Community pharmacists' attitudes towards clinical utility and ethical implications of pharmacogenetic testing. (November 2013) - Tuteja, Sony; Haynes, Kevin; Zayac, Cara; Sprague, Jon E; Bernhardt, Barbara; Pyeritz, Reed
Aim: To examine community pharmacists' attitudes towards pharmacogenetic (PGx) testing, including their views of the clinical utility of PGx and the ethical, social, legal and practical implications of PGx testing.Methods: A web-based survey administered to 5600 licensed community pharmacists in the states of Ohio and Pennsylvania (USA).Results: Of 580 respondents, 78% had a Bachelor of Science degree in pharmacy and 58% worked in a chain drug store. Doctors of pharmacy-trained pharmacists had a significantly higher knowledge score than those with a Bachelor of Science in pharmacy (3.2 ± 0.9 vs 2.6 ± 0.6; p < 0.0001). All pharmacists had positive attitudes towards PGx and most (87%) felt it would decrease the number of adverse events, and optimize drug dosing. More than half (57%) of pharmacists felt that it was their role to counsel patients regarding PGx information. Many (65%) were concerned that PGx test results may be used to deny health insurance.Conclusion: Regardless of the type of education, all pharmacists had positive attitudes towards PGx. There is still a concern among pharmacists that PGx test results may be used to deny health insurance and, thus, there is a need to educate pharmacists about legal protections prohibiting certain forms of unfair discrimination based on genotype.